2015
DOI: 10.6009/jjrt.2015_jsrt_71.3.216
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction and Implementation of Problem-based Learning for Radiography Positioning Training

Abstract: SummaryThe knowledge of radiological technologists is expected to increase with medical development. However, it is impossible to impart all knowledge in a limited time frame. Problem-based learning (PBL) is a learning methodology to solve it. In the PBL, students can gain problem-solving abilities by acquiring necessary knowledge from clinical cases and applying them during practice. We here report to implement the PBL in radiography practice. This practice opened a course at 2nd semester of third-grade stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A variety of radiology education methods have been previously reported, including problem-based learning, case-based learning, and team-based learning [4][5][6]. Unlike these previously studied conventional methods, there is a new experiential education method that enables students to practice radiology interpretation and diagnosis by taking on the radiologist's role in a simulated environment.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of radiology education methods have been previously reported, including problem-based learning, case-based learning, and team-based learning [4][5][6]. Unlike these previously studied conventional methods, there is a new experiential education method that enables students to practice radiology interpretation and diagnosis by taking on the radiologist's role in a simulated environment.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of radiology education methods have been previously reported, including problem-based learning, case-based learning, and team-based learning [11][12][13]. Unlike these previously studied conventional methods, under the concept of learning from experience, we modified a new experiential education method that enables students to practice radiology interpretation and diagnosis by taking on the radiologist's role in a simulated environment.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on a variety of radiology education models have been previously reported, including problem-based learning, case-based learning, and team-based learning [8][9][10]. Unlike these previously studied conventional methods, with the concept of learning from clinical experience, we modified a new experiential education model that enables students to practice radiology interpretation and diagnosis by taking on the radiologists' role in a simulated environment.…”
Section: Introductionmentioning
confidence: 99%